2011
DOI: 10.1007/s10551-010-0709-5
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility as a Dynamic Internal Organizational Process: A Case Study

Abstract: This article tracks Corporate Social Responsibility (CSR) as an emergent organizational process that places the employee at its center. Predominantly, research on CSR tends to focus on external pressures and outcomes leading to a neglect of CSR as a dynamic and developing process that relies on the involvement of the employee as a major stakeholder in its co-creation and implementation. Utilizing case study data drawn from a study of a large multinational energy company, we explore how management relies on emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 66 publications
2
59
0
1
Order By: Relevance
“…In summary, our findings support and extend prior CSR publications which suggested that CSR programmes should be implemented by balancing top-down and bottom-up approaches, and by considering potential spill-over effects to external constituents as well (Bolton et al 2011;Dawkins 2004;Kolk et al 2010;Van der Voort et al 2009). While these studies mainly adopted a managerial point of view, our research confirms the importance of the employees' perspective and also identifies when such trickle effects may work.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In summary, our findings support and extend prior CSR publications which suggested that CSR programmes should be implemented by balancing top-down and bottom-up approaches, and by considering potential spill-over effects to external constituents as well (Bolton et al 2011;Dawkins 2004;Kolk et al 2010;Van der Voort et al 2009). While these studies mainly adopted a managerial point of view, our research confirms the importance of the employees' perspective and also identifies when such trickle effects may work.…”
Section: Discussionsupporting
confidence: 87%
“…Although recent publications have started to pay attention to the implementation of corporate social initiatives, these are often based on the views and current (best) practices of (CSR) managers (e.g. Bolton et al 2011;Maon et al 2009;Seitanidi and Crane 2009;Sharp and Zaidman 2010;Van der Voort et al 2009), while the actual perceptions and (inter)actions of employees have remained relatively uncharted. In the case of partnerships, Berger et al (2006) explored the positive effects for employees, considering intra-and interorganisational identification as well as community and relationship building.…”
Section: Employees and Trickle Effectsmentioning
confidence: 99%
See 3 more Smart Citations